Recent Progress and Future Perspectives of Immunotherapy in Advanced Gastric Cancer - Jin, Xin; Liu, Zhaorui; Yang, Dongxiao; Yin, Kai; Chang, Xusheng (Frontiers in Immunology, 2022)
As one of the most common forms of solid tumours, gastric carcinoma has been revealed as the third leading cause of death worldwide. The symptom of gastric cancer is usually not obvious and thus difficult to detect at earlier stages. Therefore, gastric cancer is already in the advanced stage once detected in patients, which has a poor prognosis due to ineffective therapies and multiple resistance. Recent advance in understanding the microenvironment of cancer has significantly promoted the development of immunotherapy for advanced gastric cancer. Immunotherapy can induce immune responses in gastric cancer patients thus leads to the destruction of cancer cells. In comparison of traditional therapy, immunotherapy has demonstrated robust efficacy and tolerable toxicity. Therefore, this novel strategy for treatment of advanced gastric cancer has gain increasingly popularity. In this review, we summarize recent progress of immunotherapy in advanced gastric cancer, such as immune check point inhibitors, adoptive cell therapy, VEGF inhibitors, cancer vaccines and CAR-T cell therapy. We highlight immunotherapies involved in clinical applications and discuss the existing challenges of current immunotherapies and promising strategies to overcome these limitations.